Notes On The Feeding Habits of the skate Rioraja agassizi (Chondrichthyes, Rajidae) off southeastern Brazil - Pasquino, Aline F. [UNESP]; Vaske-Júnior, Teodoro [UNESP]; Gadig, Otto B.F. [UNESP]; Barreiros, João P. (My University, 2011)
Feeding habits of the skate Rioraja agassizi were analyzed in southeastern Brazil from samples obtained along Sao Paulo coast. A total of 258 specimens were examined, ranging between 96 and 532 mm total length. About 57.85% were females and 42.15% were males, resulting in a 1:1.37 sex-ratio to females. From 223 stomachs collected (94 males and 129 females) empty stomachs represented only 1.4%. Nine prey categories were identified: Polychaeta, Copepoda, Cumacea, Isopoda, Gammaridea, Dendrobranchiata, Brachyura, Teleostei, and one non-animal category (nonidentifiable items). Crustaceans were the most important item, indicating that the species has a carcinophagic preference. The presence of fish was just verified in juveniles and some adult individuals, with predominance in summer. Sex, maturity stage and seasonality did not influence the feeding habits of the species.
Keywords: Elasmobranch; Rajidae; Rioraja agassizi; SW atlantic; Trophic ecology